Kinetika Absorbsi CO2 dari Gas Emisi Kendaraan Bermotor dengan Menggunakan Absorben Monoethanolamine (MEA) pada Reaktor Gelembung Pancaran - Andanu, Wahyu; Didiek Hari Nugroho; Akbar Ismi A P (Jurnal Sains dan Ilmu Terapan, 2025)
Exhaust gas produced by motor vehicles contains several types of emissions, such as carbon monoxide (CO), hydrocarbons (HC), oxides of nitrogen (NOx), dust particles including lead (Pb), oxides of sulfur (SOx), and carbon dioxide (CO2). The content of the exhaust gas consists of about 30% carbon dioxide, 27% carbon monoxide, 25% hydrocarbons, 10% oxides of nitrogen, 9% oxides of sulfur, and 8% dust particles. Of the various types of polluting gases, carbon dioxide (CO2), carbon monoxide (CO), and hydrocarbons (HC) account for the highest percentage of harmful gases. Excessive concentrations of CO2 in the air can trigger the greenhouse effect, which contributes to an increase in atmospheric temperature and causes global warming. Carbon dioxide (CO2) in high concentrations can cause respiratory distress, although at levels below 1.5% by volume it is not considered harmful. Therefore, methods are needed to reduce air pollution, particularly that caused by CO2.